A 3D dynamic analysis of different depositing processes used in wire arc additive manufacturing. (September 2020) - Huang, Jiankang; Guan, Zhichen; Yu, Shurong; Yu, Xiaoquan; Yuan, Wen; Li, Nan; Fan, Ding
Graphical abstract: Highlights: With the increase in the deposition height, the heat dissipation changes from three-dimensional on the substrate to one-dimensional on the depositing layer. The distortion of the reverse directions can be reduced by 25 %. The stress produced by the reverse depositing model are more uniform than those produced by the same depositing model. Abstract: The complex residual stress and distortion experienced in wire arc additive manufacturing (WAAM) can have a serious impact on production. In this paper, a series of ten-layer depositing walls were deposited by WAAM using the same depositing direction and reverse depositing direction to study the effect of different heat conditions on the residual stress and distortion of the deposition wall. The temperature field, distortion, and residual stress under different paths were obtained by performing experiments. Meanwhile, to calculate the variations in the temperature, stress, and distortion under different depositing paths, a model of wire arc additive manufacturing was established by using a numerical model. The measured distortion in the same depositing directions is 25 % larger than that in the reverse directions. The stress distribution in the reverse directions is more uniform than that in the same directions. By comparison with the results from an experimental and numerical analysis, the same depositing directions have a large temperature gradient and produce greater plastic distortion during solidification.